Analysis of the Hadith “Caliphate Belongs to Guraysh” - Muradov, Safa (Scholarya Demo Journal of Ruby, 2018)
The Islamic scholars developed special rules for the right understanding of hadiths which is considred the second reliable source after the Holy Qur’an. However, interpretaions of hadiths became complicated gradually as they were considered sahih (authentic) according to the rules, and this caused dispute among scholars. One of them is the famous hadith: “Caliphate belongs to Guraysh...”. The article explores each word in the hadith text separately and attempts to define the prophet’s words expressed in the text focusing on classical hadith sources. Although most Islamic scholars have adopted the point that the Caliphate belonged to the tribe of Guraysh, the scholars disputed over the issue in the latest centuries. This reveals the necessity of reexamination of the hadith “Caliphate belong to Gureysh” that used in many sources and accepted as sahih (authentic). In addition, the article studies the companions’ reasons for not mentioning the hadith at the time of controversy and comes into conclusion that the hadith was understood differently in later periods referring to the various opinions on the issue.